Fatores associados à alteração na percepção sensorial tátil nos pés de pacientes com diabetes mellitus - Juliana Andreia Fernandes Noronha (2019)
The change in tactile sensory perception is the most prevalent neurological and microvascular complication of diabetes mellitus, often under-reported and under-treated, which may lead to an increased risk of morbidity and mortality. It is a problem that predates diabetic neuropathy, a major cause of ulceration and amputation. The objective of this study was to analyze the signs, symptoms and etiological factors of altered tactile sensory perception in patients with diabetes mellitus. A methodological study was conducted in two stages: integrative literature review and clinical validation with a cross - sectional quantitative approach. The integrative literature review was carried out from August to September 2016, in the main national and international databases, using the descriptors: diabetic neuropathies, touch, tactile perception, perceptual disorders, somatosensory disorders and nursing. Of 1371 publications identified, a sample of 23 studies was obtained that subsidized, with the pertinent variables, the instrument of data collection of the clinical stage. The publications occurred between 1992 and 2015, with higher production in the United States, with 17.3%. The studies (56.5%) were of the transverse type, with a level of evidence IV (56.5%). The clinical research was carried out in the endocrinology outpatient clinic of the reference hospital in the city of Campina Grande / PB, from May to October 2017. A pilot study was conducted to determine the reliability among raters in the data collection using the Kappa coefficient . The data collection instrument contained sociodemographic aspects, general clinical data, clinical history of diabetes mellitus and clinical evaluation of the feet through the Semmes-Weinstein monofilament test, pain sensitivity test, vibration sensitivity test with tuning fork, and aquileu reflex . A total of 224 patients were included in the study. The overall prevalence of altered tactile sensory perception was 53.1%. In the multivariate analysis, the female gender (p = 0.019), type 2 diabetes mellitus (p = 0.002), previous ulcer (p = 0.001), burning sensation (p = 0.003), cracks and fissures (p = 0.033) and Charcot's foot (p = 0.019) were associated with the presence of altered tactile sensory perception. There was a high prevalence of alteration in the tactile sensorial perception among diabetics. Early identification of signs, symptoms, and etiological factors may support nurses in the planning of evidence-based interventions for the prevention of future ulcerations and amputations.